2016
DOI: 10.3390/ijms17060918
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics and Beef Quality: A Review about Lipogenesis

Abstract: The objective of the present review is to discuss the results of published studies that show how nutrition affects the expression of genes involved in lipid metabolism and how diet manipulation might change marbling and composition of fat in beef. Several key points in the synthesis of fat in cattle take place at the molecular level, and the association of nutritional factors with the modulation of this metabolism is one of the recent targets of nutrigenomic research. Within this context, special attention has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 157 publications
(173 reference statements)
1
59
1
7
Order By: Relevance
“…Or, although fatty acid profile in the rumen is altered, does the muscle tend to maintain a pattern of their concentrations? To help answer these questions, research on how different fatty acids modulate expression of genes involved in muscle lipid metabolism have become important (Ladeira et al, 2016), of which the main results are shown in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Or, although fatty acid profile in the rumen is altered, does the muscle tend to maintain a pattern of their concentrations? To help answer these questions, research on how different fatty acids modulate expression of genes involved in muscle lipid metabolism have become important (Ladeira et al, 2016), of which the main results are shown in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The SREBF family is essential to the regulation of milk lipogenic genes expression, including acetyl-CoA carboxylase (ACC), fatty acid synthetase (FAS), stearoyl-CoA desaturase (SCD), mechanistic target of rapamycin (mTOR), desaturation fatty acid binding protein 3 (FABP3) and peroxisome proliferator activated receptor γ (PPARγ) [25]. Additionally, among the transcription factors involved in lipid metabolism of beef cattle, PPARs and SREBFs stand out [26]. …”
Section: Introductionmentioning
confidence: 99%
“…The importance of this TF for nutrigenomics in ruminants cannot be overstated since this was the first nutrigenomic effect documented. And the importance of this TF in the regulation of fat synthesis has also been observed in beef cattle and translated in marbling and meat quality [26]. A section on this commonality between dairy and beef cattle is dedicated at the end of this chapter.…”
Section: Mediators Of Nutrient-gene Interactions In Ruminantsmentioning
confidence: 90%
“…Nutrigenomics study the interactions between nutrients and genes [85], that is how the nutrients present in the diet can affect gene expression. In beef animals, nutrigenomics was widely studied [26]; following, a more detailed description of how specific nutrients regulate the expression of genes related to muscle growth and intramuscular fat deposition will be addressed.…”
Section: Nutrigenomics In Beef Cattlementioning
confidence: 99%